2014
DOI: 10.1111/jdv.12377
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, patient‐reported outcomes and safety profile of ATX‐101 (deoxycholic acid), an injectable drug for the reduction of unwanted submental fat: results from a phase III, randomized, placebo‐controlled study

Abstract: BackgroundUnwanted submental fat (SMF) may result in an unattractive chin profile and dissatisfaction with appearance. An approved and rigorously tested non-surgical method for SMF reduction is lacking.ObjectiveTo evaluate the efficacy and safety of ATX-101 for the pharmacological reduction of unwanted SMF in a phase III randomized, double-blind, placebo-controlled study.MethodsPatients (n = 360) with moderate or severe SMF were randomized to receive ATX-101 1 or 2 mg/cm2 or placebo injected into their SMF for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
2
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(133 citation statements)
references
References 24 publications
4
119
2
8
Order By: Relevance
“…10 The patient population was also similar, with the majority of patients being white and female (Table 1). (2) is defined as prominent, localized SMF, and severe (3) is defined as marked, localized SMF.…”
Section: Discussionmentioning
confidence: 87%
“…10 The patient population was also similar, with the majority of patients being white and female (Table 1). (2) is defined as prominent, localized SMF, and severe (3) is defined as marked, localized SMF.…”
Section: Discussionmentioning
confidence: 87%
“…Patients satisfaction with the treatment received was scored by subject global questions ('a great deal worse' to 'a great deal better', 'extremely dissatisfied' to 'extremely satisfied'). In this study protocol, SLRS was classified as 'other efficacy outcome' not 'secondary efficacy outcome' [38].…”
Section: Atx-101mentioning
confidence: 99%
“…Phase II, multicenter, randomized, double-blind, placebo-controlled, parallel-group study of the safety and efficacy of ATX-101 (NCT00618618) . Interventional nonrandomized long-term, follow-up study of patients who completed Phase III trials of ATX-101-10-16 or ATX-101-10-17 (NCT02052622) [31][32][33][34][35][36][37][38][39].…”
Section: Clinical Trials With Atx-101mentioning
confidence: 99%
“…The mechanism of action of this injection is through its bile acid properties of emulsifying and solubilising fat. The product promotes adipocyte lysis through disruption of the cell membrane [16,17]. The REFINE-1 and REFINE-2 studies demonstrated that ATX-101 significantly reduced submental fat in comparison to placebo.…”
Section: Editorialmentioning
confidence: 99%
“…Furthermore, patients reported a high level of selfperceived improvement after the treatment [18]. The product was generally well-tolerated with few patients reporting adverse events [16,18].…”
Section: Editorialmentioning
confidence: 99%